2012
DOI: 10.1007/s00439-012-1246-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interactions and obesity traits among postmenopausal African-American and Hispanic women in the Women’s Health Initiative SHARe Study

Abstract: Genome-wide association studies of obesity measures have identified associations with single nucleotide polymorphisms (SNPs). However, no large-scale evaluation of gene-environment interactions has been performed. We conducted a search of gene-environment (G×E) interactions in post-menopausal African-American and Hispanic women from the Women’s Health Initiative SNP Health Association Resource GWAS study. Single SNP linear regression on body mass index (BMI) and waist-to-hip circumference ratio (WHR) adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 65 publications
0
34
0
2
Order By: Relevance
“…A genetic marker near Cntnap2 would be associated with profoundly different effects on body weight in a segregating cross and would therefore appear to have no consistent effect. For this reason, it is striking that a GWAS study for obesity-related traits in humans identified a SNP (rs4549702) in CNTNAP2 that was associated with increased body weight in an AfricanAmerican population but decreased body weight in a Hispanic population (Velez Edwards et al 2012). Had the populations not been stratified, the effect of this SNP may have been overlooked.…”
Section: Epistasismentioning
confidence: 99%
“…A genetic marker near Cntnap2 would be associated with profoundly different effects on body weight in a segregating cross and would therefore appear to have no consistent effect. For this reason, it is striking that a GWAS study for obesity-related traits in humans identified a SNP (rs4549702) in CNTNAP2 that was associated with increased body weight in an AfricanAmerican population but decreased body weight in a Hispanic population (Velez Edwards et al 2012). Had the populations not been stratified, the effect of this SNP may have been overlooked.…”
Section: Epistasismentioning
confidence: 99%
“…Vélez y colaboradores (23) señalaron que existen diferencias étnicas en las interacciones de genes implicados en procesos metabólicos y corporales que modifican el impacto de las exposiciones ambientales; no obstante, aclaran que es necesario realizar estudios que lo verifiquen. Observamos que el sobrepeso y la obesidad se asociaron a peor CV comparados con el IMC normal, tal como previamente se halló en una gran cohorte de colombianas (3) .…”
Section: Discussionunclassified
“…Las preguntas se agrupan en cuatro dominios: menopausia/salud (incluye tres subdominios: síntomas vasomotores, salud y envejecimiento), psíquico, sexualidad y relación de pareja. Cada pregunta es tipo Likert: 0 [no presente], 1-2-3-4 [intermedios] y 5 [mucho], siendo de mejor a peor en las preguntas negativas [1, 2,3,5,6,7,9,10,11,12,14,16,17,18,19,21,23,24,25,27,28,29, 31] y lo contrario en las positivas [4,8,13,15,20,22,26,30]. Las sumas crean el puntaje de los dominios y entre estos el global, que va de 0 a 155.…”
Section: Cavimec [Calidad De Vida En La Menopausia Yunclassified
“…In addition to unidentifi ed rare variants ( 28 ), genetic interactions, both gene-by-gene between loci and GxE have been proposed to explain some of this missing heritability ( 28 ). Recent examples of genes interacting with dietary intake have been identifi ed for obesity traits ( 29,30 ). Accordingly, in this study we have demonstrated a novel and replicated fi nding that common variants at APOB in males and females (rs2678379, P = 2.92 × 10 Ϫ 5 ) and NPC1L1 in males only (rs17725246, P = 2.20 × 10 Ϫ 3 ) demonstrate GxE interactions with dietary cholesterol intake in the prediction of total cholesterol.…”
Section: Discussionmentioning
confidence: 99%